On Material Indeterminacy. Issue 2 (4th May 2022) - McLaughlin, Scott
Abstract : 'Material indeterminacy' is the term I use to discuss how my work since 2010 has explored the consequences of placing materiality, indeterminacy, and responsiveness at the centre of a compositional practice, and what means for the relationships between instrument, player, and score. I propose that the structural consequence of contingency in instrumental performance is an underexplored aspect of experimental composition, which has historically tended to focus on models that either control contingency or obviate its consequences. 'Material indeterminacy' is proposed as a third way that folds the emergent consequences of contingency back into meaningful relation with the unfolding structure. This research is framed by theoretical perspectives on materiality: Andrew Pickering's performative ontology of human and material agencies, specifically his 'dance of agency' between human and material; anthropologist Tim Ingold's phenomenological approach to materiality that valorises the relational 'working-with' of human and material. The liveliness of materiality is considered in relation to Lucy Suchman's work on situatedness and the entwined nature of plans and actions, and then returned to a musical context via listening and the discourse of improvisation as response-to-contingency. Finally, I discuss these ideas via examples of my own work from the Garden of Forking Paths compositional project (2019–2021).